Proteocephalid tapeworms (Cestoda: Onchoproteocephalidea) of loaches (Cobitoidea): Evidence for monophyly and high endemism of parasites in the Far East - Scholz, Tomáš; de Chambrier, Alain; Shimazu, Takeshi; Ermolenko, Alexey; Waeschenbach, Andrea (Parasitology international, 2017)
The parasite fauna of loaches (Cypriniformes: Cobitoidea), a group of small bottom-dwelling freshwater fishes with a mostly Eurasian distribution, remains a largely unknown quantity. Here we revise the taxonomy of tapeworms of the genus Proteocephalus Weinland, 1858 (Cestoda: Proteocephalidae) that had been found in loaches from the Palaearctic Region (Central Europe, Japan and Russia [Primorsky Region]). Molecular phylogenetic analysis based on two nuclear (ssr- and lsrDNA) and two mitochondrial genes (cox1 and rrnL) revealed a monophyletic group consisting of four valid species nesting within the Proteocephalus-aggregate: (i) Proteocephalus sagittus (Grimm, 1872) from Barbatula barbatula (Europe, Russia and Tajikistan), (ii) Proteocephalus demshini n. sp. from Barbatula toni (Russian Far East - Primorsky Region), (iii) Proteocephalus midoriensis Shimazu, 1990 from Lefua echigonia (Japan) and L. costata (Russia) (new host and geographical record), and (iv) Proteocephalus misgurni n. sp. from Misgurnus anguillicaudatus (Russia; Primorsky Region). Proteocephalus sagittus and P. demshini, and P. midoriensis and P. misgurni were recovered as sister taxa, respectively. Proteocephalus sagittus and P. demshini are characterized by having proglottids that are wider than long, an elongate to pyriform cirrus-sac and the vitelline follicles that form wide lateral bands. Proteocephalus midoriensis and P. misgurni are characterized by having proglottids that are more elongate and an ovoid to almost spherical cirrus-sac and the vitelline follicles forming narrow lateral bands. Proteocephalus demshini differs from P. sagittus in the posterolateral extent of the vitelline follicles, whereas P. misgurni can be distinguished from P. midoriensis mainly by the relative size of the ovary, posterior extent of the vitelline follicles and width of the scolex. Unlike most species of the Proteocephalus-aggregate that possess an apical sucker, all species from loaches are devoid of any apical organ. The existence of two new species in loaches from the Primorsky Region of Russia indicates high endemism of fish parasites in this region. A key to the identification of recognized species from loaches is provided.
Keywords: Animals; Dálný východ; endemické nemoci; Cestoda; DNA, Mitochondrial; cestodózy; RNA, Ribosomal, 16S; nemoci ryb; Fish Diseases; máloostní; Phylogeny; Asia, Eastern; Endemic Diseases; mitochondriální DNA; Cypriniformes; Cestode Infections; zvířata; fylogeneze; RNA ribozomální 16S